The family business succession model: an exploratory analysis of factors impacting family business succession preparedness - Coffman, Brett A. (Kansas State University, 2013)
The efficient operation and succession of family owned businesses plays a critical role in our national economic health. This study was built upon the Family Business Succession Model, which is based on family systems theory. The impact of owner characteristics, enterprise characteristics, business formalizing activities, family influence, access to resources, and external environmental conditions, all on the extensiveness of family business succession preparedness, was assessed. These results were moderated by the generation of the business. With an exploratory and descriptive methodology, primary survey data were obtained from family business owners in Missouri, Illinois, and Kansas. Research results provide family business advisors with important insight for developing recommendations around improving the extensiveness of family business succession preparedness, provide important policy implications, and serve as a basis for additional theory development in family business succession planning.
Keywords: Family business; Family business succession model; Family dynamics; Business succession; Business formality; Succession preparedness; Behavioral Sciences (0602); Business (0310); Economics (0501)